THE IMPACT OF THE ABOLITION OF CORPORAL PUNISHMENT ON ETHICS AND DISCIPLINE AMONG STUDENTS AT THE NURUL IKHLAS MODERN ISLAMIC BOARDING SCHOOL - Mubarik Baeha, Musfi; Rustim, Rustim; Premier Zega, Frendy (Academic Journal Research, 2025)
Objective: This study investigates the impact of eliminating corporal punishment on students’ ethical behavior and disciplinary patterns at Nurul Ikhlas Modern Islamic Boarding School (PPMNI). Method: Employing a qualitative approach, data were collected through direct observation, interviews with school leaders and caregivers, and analysis of institutional documents. Results: The findings indicate that while the former use of corporal punishment contributed to a heightened sense of discipline, its abolition has led to a decline in students’ ethical behavior, despite an observable improvement in their external compliance with school rules. This suggests a shift from internalized values to superficial conformity. The study highlights that non-physical disciplinary strategies have not fully succeeded in fostering the same depth of moral development. Novelty: This research contributes to the discourse on school discipline by revealing the nuanced consequences of banning corporal punishment in religious educational settings and by emphasizing the need for structured ethical and spiritual reinforcement to sustain moral integrity in the absence of physical discipline.